2023
DOI: 10.1021/acs.jpca.3c00482
|View full text |Cite
|
Sign up to set email alerts
|

Production of Molecular Iodine via a Redox Reaction between Iodate and Organic Compounds in Ice

Abstract: The abiotic mechanism of molecular iodine (I 2 ) production from iodate (IO 3 − ) remains largely unknown. Here, we demonstrate the production of I 2 in the presence of IO 3 − and organic compounds in ice. When the solution containing IO 3 − (100 μM) and furfuryl alcohol (100 μM) at pH 3.0 was frozen at −20 °C, 13.1 μM of I 2 was produced with complete degradation of furfuryl alcohol after 20 min. However, there was little change in the IO 3 − and furfuryl alcohol concentrations in water at 25 °C. The producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Besides, the iodine species in SCU‐CPN‐6‐I are classified as the reduced state (I − ) and the intermediate state (I 2 ) rather than the oxidation state as IO 3 − (V) in I 3d XPS spectrum (Figure 5b), indicating that IO 3 − is reduced after being adsorbed to SCU‐CPN‐6 in aqueous solution. This finding is closely similar to the research reported on the reduction of IO 3 − by furfuryl alcohol [38] . In addition, partial C−O converts to C=O in SCU‐CPN‐6‐I (Figure 5d), concomitant with no obvious changes observed for other elements of SCU‐CPN‐6.…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…Besides, the iodine species in SCU‐CPN‐6‐I are classified as the reduced state (I − ) and the intermediate state (I 2 ) rather than the oxidation state as IO 3 − (V) in I 3d XPS spectrum (Figure 5b), indicating that IO 3 − is reduced after being adsorbed to SCU‐CPN‐6 in aqueous solution. This finding is closely similar to the research reported on the reduction of IO 3 − by furfuryl alcohol [38] . In addition, partial C−O converts to C=O in SCU‐CPN‐6‐I (Figure 5d), concomitant with no obvious changes observed for other elements of SCU‐CPN‐6.…”
Section: Figuresupporting
confidence: 91%
“…À by furfuryl alcohol. [38] In addition, partial CÀ O converts to C=O in SCU-CPN-6-I (Figure 5d), concomitant with no obvious changes observed for other elements of SCU-CPN-6. The phenol groups in SCU-CPN-6 were transformed into benzoquinone, which is the primary cause that makes IO 3 À reduced, bearing a resemblance to the phenol reduction effect to uranyl ions in Redox-COF1.…”
Section: Zuschriftenmentioning
confidence: 88%
“…The reductive conversion of iodate by FA under dark or irradiated conditions at an initial pH (pH i ) 3.0 is shown in Figure . A small fraction of iodate (<10%) can be reduced by FA in frozen solution under a dark condition after 24 h. Kim et al reported that freezing enhanced the degradation of some organic pollutants by iodate, indicating that iodate can exhibit stronger oxidative reactivity in ice. The reductive activity of FA in ice was also reported in our previous work on the freezing-enhanced reduction of bromate under dark condition .…”
Section: Resultsmentioning
confidence: 99%
“…22,25−28 Gaĺvez et al 29 revealed that the photolysis of frozen iodate salts in the presence of low water content (@100−253 K) serves as a source of RI. Most recently, Kim et al 30 reported that freezing the iodate solution in the presence of various organic pollutants enhances the production of molecular iodine under dark condition, which indicates the accelerated reaction between iodate and organic substances in ice. It has also been reported that freezing enhances bromate reduction by NOM under both dark and light conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation